Observation of a Be double-Lambda hypernucleus in the J-PARC E07 experiment. (22nd February 2019) - Ekawa, H; Agari, K; Ahn, J K; Akaishi, T; Akazawa, Y; Ashikaga, S; Bassalleck, B; Bleser, S; Endo, Y; Fujikawa, Y; Fujioka, N; Fujita, M; et al.
Abstract: A double-Λ hypernucleus, _ΛΛBe, was observed by the J-PARC E07 Collaboration in nuclear emulsions tagged by the (K^-, K^+ ) reaction. This event was interpreted as the production and decay of _ΛΛ^ 10Be, _ΛΛ^ 11Be, or _ΛΛ^ 12Be^* via Ξ^- capture in ^16O . By assuming capture in the atomic 3D state, the binding energies of two Λ hyperons (B_ΛΛ ) of these double-Λ hypernuclei are obtained to be 15.05 ± 0.11 MeV, 19.07 ± 0.11 MeV, and 13.68 ± 0.11 MeV, respectively. Based on the kinematic fitting, _ΛΛ^ 11Be is the most likely explanation for the observed event.